A Convenient Route to 2-Bromo-3-chloronorbornadiene and 2,3-Dibromonorbornadiene - Lennartson, Anders; Quant, Maria; Moth-Poulsen, Kasper (Synlett, 2015)
Substituted norbornadienes are useful in a wide range of applications, including molecular solar-thermal (MOST) energy storage systems. An important precursor for 2,3-substituted norbornadienes is 2-bromo-3-chloronorbornadiene, where the two halogen atoms can be substituted selectively through two consecutive Suzuki cross-coupling reactions. Previous routes to 2-bromo-3-chloronorbornadiene have used 1,2-dibromoethane as a brominating agent, a substance known to be carcinogenic and the use of which is restricted in certain countries. Herein is reported a one-pot route to 2-bromo-3-chloronorbornadiene in 50% yield using p-toluenesulfonyl bromide as a bromine source. In addition, the procedure has been adapted to allow synthesis of 2,3-dibromonorbornadiene in 37% yield.
Keywords: bromine; chlorine; organometallic reagents; regioselectivity; alkenes